Still on the map? Considering regional historiography of music - Hochradner, Thomas (Muzikološki zbornik, 2020)
The paper aims to re-evaluate regionality as a key concept in musicology. After a short introduction to the topic, a case study on Salzburg is presented, followed by critical remarks on relevant literature and a summary that attempts to redefine the significance of regional and local developments within the discipline.
Keywords: case study; glasbeno zgodovinopisje; music historiography; musicology; regionality; regionalnost; Salzburg; študija primera